IMPROVING DESCRIPTIVE WRITING THROUGH 'VK'S PROJECT' AUDIOVISUAL: A QUASI-EXPERIMENTAL STUDY - Selfiana Enjelia; Puput Zuli Ekorini (Journal of English Language Education, 2025)
Many young people today frequently use more than one language, often mixing Indonesian with English in both oral and written communication. At MTs Al-Huda Gondang, a problem identified is students' lack of proficiency in constructing proper sentences, describing objects or events in detail, and understanding the correct structure of descriptive texts. This research aims to determine whether there is a significant difference in the descriptive text writing skills (on the topic of animals) of Grade VII students at MTs Al-Huda Gondang before and after the use of the "Vk's Project" audiovisual media in the learning process. This study employs a quantitative approach with a one-group pre-test-post-test experimental design. Data were collected twice using a pre-test (before treatment) and a post-test (after treatment) to compare students' writing skills. The sampling technique was convenience sampling. The results showed a mean pre-test score of 61.31 and a post-test score of 80.52. In the pre-test, 17 students (89%) scored below the minimum mastery criterion (KKM) of 75. In the post-test, 18 students (95%) achieved scores at or above the KKM. Data analysis using a paired sample t-test revealed that t_count > t_table (10.11 > 1.734), leading to the acceptance of the alternative hypothesis (Ha). Furthermore, the effect size calculation (Cohen's d = 2.32) indicates a very large practical significance. Therefore, it is concluded that the use of the "Vk's Project" audiovisual significantly improved students' descriptive text writing skills about animals. It is acknowledged that the study's design, lacking a control group, limits the ability to definitively attribute all improvement solely to the intervention..